2019
DOI: 10.1101/783829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunization of mice with chimeric antigens displaying selected epitopes confers protection against intestinal colonization and renal damage caused by Shiga toxin-producingEscherichia coli

Abstract: Shiga toxin-producing Escherichia coli (STEC) cause diarrhea and dysentery, which may progress to hemolytic uremic syndrome (HUS). Vaccination has been proposed as a preventive approach against STEC infection; however, there is no vaccine for humans and those used in animals reduce but do not eliminate the intestinal colonization of STEC. The OmpT, Cah and Hes proteins are widely distributed among clinical STEC strains and are recognized by serum IgG and IgA in patients with HUS. Here, we develop a vaccine for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…LAA presence is associated with severe human disease and although the mechanisms used by LEE-negative STEC strains to colonize the human intestine are not clear yet [17]. Recently, the role of LAA in intestinal colonization was demonstrated in a murine model of STEC infection, suggesting that LAA may be also involved in the adherence of STEC to the human intestine [18,19]. Moreover, the association of LAA with stx1a, stx2a, stx2d and cdtB toxin genes that cause severe disease has been demonstrated [18].…”
Section: Introductionmentioning
confidence: 99%
“…LAA presence is associated with severe human disease and although the mechanisms used by LEE-negative STEC strains to colonize the human intestine are not clear yet [17]. Recently, the role of LAA in intestinal colonization was demonstrated in a murine model of STEC infection, suggesting that LAA may be also involved in the adherence of STEC to the human intestine [18,19]. Moreover, the association of LAA with stx1a, stx2a, stx2d and cdtB toxin genes that cause severe disease has been demonstrated [18].…”
Section: Introductionmentioning
confidence: 99%
“…6B). Some studies revealed that IgG in the murine intestine leads to the elimination of the Shiga toxin-producing Escherichia coli , virulent Citrobacter rodentium , and rotavirus 27, 42, 43 . The vaccines against H. pylori were also vaccinated by systemic immune routes such as intramuscular immunization 44, 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the OmpT protein participates in different mechanisms of pathogenicity in STEC and therefore is a promising target for vaccine development [ 62 ]. In fact, a recently developed vaccine candidate against STEC includes epitopes and antigenic domains of this protein [ 63 ]. Notably, this vaccine candidate confers protection on mice against the intestinal colonization and renal damage caused by STEC.…”
Section: Discussionmentioning
confidence: 99%